GAMBARAN FAKTOR RENDAHNYA KONSUMSI TABLET FE IBU HAMIL TRIMESTER III DI DESA KRANJINGAN KECAMATAN SUMBERSARI KABUPATEN JEMBER - Stefani Maulidya Restianti (LPPM Universitas dr. Soebandi, 2015)
Anemia is a condition of the mother with hemoglobin (Hb) levels in her blood less than 12 gr%. Giving Fe tablets is one of the important efforts in preventing and overcoming anemia. In East Java it is estimated that 37.6% of anemia pregnant women. In Jember, 55% of pregnant women have anemia. The purpose of this study was to determine the description of the factor of low consumption of fe tablets for third trimester pregnant women in Kranjingan Village, Sumbersari District, Jember Regency. This type of research is descriptive. The population in this study was the third trimester pregnant women amounted to 59 large samples in this study were 37 people with the sampling technique used was purposive sampling. Data were analyzed using computers with Statistical Product and Service Solutions (SPSS). The results showed that the factor of low consumption of trimester III pregnant women fe tablets in Kranjingan Village, Sumbersari Subdistrict, Jember Regency was possible because most of the third trimester pregnant women education was SMP 23 (62.2%), having 2 times 15 (40.5%) pregnancy examinations, and mother's level of knowledge is in the sufficient category that is 22 (59.5%). Factors causing the low consumption of Fe tablets in third trimester pregnant women are due to low education, lack of examination frequency and sufficient knowledge about Fe tablets. The conclusion in this study is that the tendency for low consumption of Fe tablets is due to education, frequency of pregnancy checks and knowledge. So that efforts are needed to increase knowledge by seeking information from health workers or print and electronic media, as well as increasing pregnancy checks.